Language learning strategy use among Iranian engineering EFL learners - Nahavandi, Naemeh; Mukundan, Jayakaran (Australian International Academic Centre, 2014)
The present study aimed at understanding the language learning strategy use of Iranian EFL learners’ about learning a foreign language. The main purpose of the study was to understand if there was any relationship between proficiency level, gender and extra education in language institutes and strategy use. To achieve this end, 369 engineering students were selected based on random sampling in Azad University of Tabriz, Iran. Data were collected using two questionnaires: a demographical questionnaire and the Strategy Inventory for Language Learning (SILL). ANOVA, LSD & t-test were used for analyzing the data. The results of the study indicated highest mean average of metacognitive (M=3.57), followed by social (M=3.27), cognitive (M=3.12), compensation (M=3.07), memory (M=2.89) and affective (M=2.84) strategies. Furthermore, the results indicated a significant difference among learners’ strategy use, proficiency level and extra education in language institutes. Nevertheless, no significant difference was found between learners’ strategy use and gender. The study ended with some pedagogical implications.